Cellulose nanofibrils/chitosan based transdermal drug delivery vehicle for controlled release of ketorolac tromethamine. (20th November 2017) - Sarkar, Gunjan; Orasugh, Jonathan T.; Saha, Nayan R.; Roy, Indranil; Bhattacharyya, Amartya; Chattopadhyay, Atis K.; Rana, Dipak; Chattopadhyay, Dipankar
Abstract : Cellulose nanofibrils (CNFs) have attracted attention as a promising material in the biomedical field because of their outstanding properties such as hydrophilicity, biocompatibility, biodegradability, and high surface area. Abstract : Cellulose nanofibrils (CNFs) have attracted attention as a promising material in the biomedical field because of their outstanding properties such as hydrophilicity, biocompatibility, biodegradability, and high surface area. In this work, we have prepared cellulose nanofibrils from jute fibres (JF), to develop a CNF/chitosan transdermal film for the delivery of ketorolec tromethamine (KT) where the CNFs act as an elegant nanometric carrier. The KT-loaded CNF/chitosan transdermal film matrices have been characterized by Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis. Fourier transform infrared spectroscopy (FTIR) reveals the successful KT loading into the CNF/chitosan transdermal film. Scanning electron microscopy (SEM) study shows the different morphological features of the CNF/chitosan transdermal films. The crystalline nature of the CNF/chitosan transdermal films has been analyzed by X-ray diffraction study. Release profiles from the CNF/chitosan matrices indicate that the drug release rate is sustained with the incorporation of CNFs. We believe that this new nanocarrier may be a potential choice for transdermal drug delivery systems.